Analyzing Formative Test Results for Descriptive Questions on Paragraph Main Ideas in Elementary Students. - Aulia Pramudani; Hetilaniar H; Susanti Faipri Selegi (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
This study aims to analyse the achievement of formative test results of fifth grade students on the main idea of paragraphs based on Bloom's taxonomy (C1-C6) in elementary schools. This study uses a descriptive quantitative approach. The subjects of this study were 15 students of grade V.B of SD Negeri 1 Makarti Jaya. The instrument used was a formative test in the form of essay questions arranged based on Bloom's taxonomy cognitive level. The research data were obtained through formative test results which were then analyzed using descriptive statistics and percentage of achievement. The results showed that the average score of students was 75 with a median of 77, mode of 75, minimum score of 37, and maximum of 95, and a standard deviation of 17.8. A total of 11 students had achieved learning mastery, while 4 students had not yet completed and needed remedial. After remedial and enrichment, the final results showed that 13 students (86.67%) were in the very good category and 2 students (13.33%) were in the good category. Based on the cognitive level analysis, students' abilities at the low to intermediate levels (C1–C3) are classified as good, while those at the high levels (C4–C6) still need improvement. Thus, it can be concluded that students' formative test results on the main idea of paragraphs are generally in the good category, but efforts are needed to improve higher-order thinking skills.